The Role of Visit Activities in Preventing Vehicle Theft Criminal Action in Jember Police Region - Rio Dharmawan (Advances in Police Science Research Journal, 2021)
This study was caused by the increase of vehicle theft cases in the Jember police area during the period from January 2018 - December 2020. The problems of this study discussed the role of the Binmas Unit in preventing vehicle theft and the factors that influenced the visit implementation by the Binmas Unit. The purpose of this study is to explain and analyze the Binmas Unit's role in preventing the occurrence of vehicle theft by visit activities and explain the factors that influenced the visit activities to prevent vehicle theft. This study uses a qualitative method. The data used are primary data and secondary data. The methods of collecting the data were interviews, observation, and review of documents. From the results of this study, the fact of several things has not been fulfilled by the Binmas Unit members as stated in attachment B of the Police Chief Regulation Number 3 of 2015 concerning Community Policing. The Binmas Unit members have not prepared yet their id cards, visit format, security and community order (kamtibmas) brochures/leaflets, and as well as contacting residents who will be visited first. The implementation of the visit activity is also influenced by supporting and inhibiting factors. The conclusion from this study is the visit activity enough with the Binmas Unit member's available budget, however, there is still no regulation to regulates the visit activity implementation so this activity is considered less effective. The writer suggests the Binmas Unit member need to be given appreciation for those who have more achievements, abilities and minimize the members present who have concurrent duties.